Strengthening seed systems and market development in Kenya: Perspectives on political economy and policy processes - Ayieko, Miltone; Odame, Hannington; Olwande, John (Tegemeo Institute of Agricultural Policy and Development, 2021)
Seed systems in Africa south of the Sahara are a topic of much interest in the public discourse on policy options for agriculture and rural development. The seed systems of countries in the region have followed different trajectories that can be partly explained by differences in farming systems, agroecological conditions, stages of market development, and other variables. But political economy factors may also play an important role in outcomes. This study uses a political economy lens to assess the pace and dynamics of policy change and how those factors affect the development of maize and potato seed systems and of markets in Kenya. We review key policy, regulatory, and strategic documents relevant to seed system and market development in Kenya. We then review progress made in strengthening those seed systems and markets and examine the political economy factors that have influenced policy adoption and outcomes. Findings suggest that Kenya’s devolution process and the Jubilee government’s Big Four Agenda—alongside political economy factors related to agricultural extension, seed regulations, and public financing—have had and continue to have a considerable effect on the implementation of various policies, potentially constraining progress on several fronts.